The New York Times on The NATO bombing of FR Yugoslavia in 1999 - Savić Aleksandra (Srpska Politička Misao)
This paper examines the daily reporting by The New York Times on the bombing of Yugoslavia. The research corpus is based on articles published from March 24, 1999, to June 10, 1999. This study aims to determine how the bombing itself is represented in the media and which linguistic tools are used to construct the image of Serbs. Furthermore, the paper provides an overview of significant publications that represent the perception of both the foreign and domestic press regarding NATO's military action. The paper's first hypothesis is that Serbia's negative image is constructed mainly at the lexical and stylistic levels of the language. The second hypothesis is that the articles in The New York Times fully correspond with the representation of Serbs and Serbia in other European and global media. Actually, together with them, they can be interpreted as part of a unique transnational discourse. The main characteristics of this global narrative include: mitigating the impact and consequences of the bombing, building a negative image of the Serbian nation, simplifying complex historical and political relations, and demonizing the enemy. Our research showed that The New York Times uses mitigated vocabulary, descriptive constructions, and many euphemisms for the bombing. The goal of this use is to hide the real picture of the military operation and to prevent the appearance of empathy in people's eyes. Because of this, it is possible to count on voters approval or greater support for the state's foreign policy and gain international legitimacy for military intervention. The most extreme example of mitigated vocabulary is the depiction of bombings as fireworks, which not only attempts to cover up the violence and suffering of innocent people but also turns it into a celebration. Additionally, beyond the stereotypical depiction of the military attacks themselves, the relationship between the two opposing sides is portrayed in a clichéd and simplified manner. A negative attitude towards an entire nation, its past, and its main characteristics is used to justify increasingly inhumane targets for NATO bombs. The demonization of Serbs is further reinforced by the use of metaphors that simplify complex historical, political, and ethnic relations, reducing them to a matter of external control. An identical discourse appears in the German, British, and American media.